IoT-based intelligent irrigation management and monitoring system using arduino - Fidaus Kamaruddin; Nik Noordini Nik Abd Malik; Noor Asniza Murad; Nurul Mu’azzah Abdul Latiff; Sharifah Kamilah Syed Yusof; Shipun Anuar Hamzah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Plants, flowers and crops are living things around us that makes our earth more productive and beautiful. In order to growth healthy, they need water, light and nutrition from the soil in order to effect cleaning air naturally and produce oxygen to the world. Therefore, a technology that manage to brilliantly control plants watering rate according to its soil moisture and user requirement is proposed in this paper. The developed system included an Internet of Things (IoT) in Wireless Sensor Network (WSN) environment where it manages and monitors the irrigation system either manually or automatically, depending on the user requirement. This proposed system applied Arduino technology and NRF24L01 as the microprocessor and transceiver for the communication channel, respectively. Smart agriculture and smart lifestyle can be developed by implementing this technology for the future work. It will save the budget for hiring employees and prevent from water wastage in daily necessities.